The degree to which strategic leadership is practiced and its relationship to crisis management in the Public Broadcasting Corporation in the southern governorates Southern - Abu Hilal, (Ramzi (Mohammed Nader (Journal of Economic, Administrative and Legal Sciences, 2025)
The objective of the present study was to ascertain the extent to which strategic leadership practices were implemented, and to establish their relationship with crisis management in the Public Authority for Radio and Television in the southern governorates. In order to accomplish the aforementioned objectives, the researcher employed a combination of descriptive and analytical methods and utilized a questionnaire as the primary instrument for data collection. The study population comprised all employees of the Authority from the leadership and supervisory levels in the southern governorates of the study, with a total of 450 employees. To determine the study sample, a stratified random sampling method was employed, resulting in a sample of 208 individuals. The SPSS statistical package was utilized for data analysis and the calculation of appropriate statistics. The study yielded several key findings: - First, the study demonstrated the availability of strategic leadership dimensions among employees of the Palestinian Radio and Television Authority in the southern governorates to a great degree, and the existence of positive attitudes among the study population towards the dimensions of strategic leadership, which confirms their understanding of the concept. - Second, the study showed a high level of agreement by the sample members on the paragraphs of the crisis management axis among employees of the Public Authority for Radio and Television in the southern governorate. - Third, the study results showed that the dimensions of strategic leadership have a fundamental and statistically significant impact on improving crisis management, explaining 43.7% of the level of crisis management among employees of the General Authority for Radio and Television in the southern governorates. This means that strategic leadership plays an important and fundamental role in determining the level of the dependent variable (crisis management) among employees in the institutions under study, and that the remaining variability may be due to other factors outside the scope of the study. The study yielded several recommendations, including: - Top management should not only take decisions to solve existing issues, but also take proactive decisions to prevent future issues from occurring. - Granting managers of organizations, the powers that enable them to respond to changing circumstances.
Keywords: Strategic Leadership; Crisis Management; Public Authority for Radio and Television